Financial inclusion and extreme poverty in the MENA region: a gap analysis approach. Issue 3 (2nd July 2020) - Emara, Noha; Mohieldin, Mahmoud
Abstract : Purpose: Eradicating extreme poverty remains one of the most significant and challenging sustainable development goals (SDGs) in the Middle East and North African (MENA) region. The latest World Bank statistics from 2018 show that extreme poverty in MENA increased from 2.6% to 5% between 2013 and 2015. MENA ranks third among developing regions for extreme poverty and fell short of halving extreme poverty by 2015 – the target established by the United Nations' (UN) millennium development goals, the precursor to the SDGs. The purpose of this study is to analyze the impact of financial inclusion on extreme poverty for a sample of 34 countries over the period 1990–2017. Design/methodology/approach: Using system general method of moments dynamic panel estimation methodology on annual data for 11 MENA countries and 23 emerging markets (EMs) over the period 1990 – 2017, this study begins by estimating the impact of financial inclusion – using measures of access and usage – on the eradication of extreme poverty by 2030, the first goal of the SDGs. Findings: The results of the study indicate that, on one hand, financial access measures have a positive, statistically significant impact on reducing extreme poverty for the full sample and the MENA region. The second part of the study uses a gap analysis against four poverty targets – 0%, 1.5%, 3% and 5% – and shows that no MENA country and few EM countries will be able to close the extreme poverty gap and reach the target of 0% by 2030 by depending solely on improvements in financial access. These targets are based on the two benchmarks set by the World Bank and the UN, with intermediaries to capture error and give a fuller picture of what is possible. However, if improvements in financial inclusion alone can bring every EM and MENA country except Djibouti and Romania to bring the most accessible target of reducing global extreme poverty to no more than 5% by 2030. Originality/value: While research on poverty reduction in the region tends to focus on financial development and governance, less attention has been paid to the role of financial inclusion. SDG 1 – eliminating poverty in all its forms – explicitly highlights the importance of access to financial services. Indeed, evidence from Argentina, India, Kenya, Malawi, Niger and other countries demonstrates the ways in which financial inclusion can impact poverty (Klapper, El-Zoghbi and Hess, 2016). When people are included in the financial system, they are better able to improve their health, invest in education and business and make choices that benefit their entire families. Financial inclusion advances governments, too: introducing vast segments of the population into the financial system by digitizing social transfers, for example, can cut government costs and reduce leakage, with benefits that ripple across society. Yet, the links between financial inclusion and poverty reduction in MENA are less established. This study aims to analyze the importance of financial inclusion in addressing extreme poverty by 2030, the year UN member states set as a target for achieving the SDGs.